CONSUMERS’ LEGAL PROTECTION CERTAINTY VIS-À-VIS THE APPLICATION OF STANDARD CONTRACTS - I Putu Pasek Bagiartha (Jurnal IUS Kajian Hukum dan Keadilan, 2013)
The consumer protection is an important aspect to ensure the legal certainty for consumersin using products of marketed businesses. Orientations of entrepreneurs is emphasize thepracticality of achieving profits to encourage the growth of unhealthy trade practices with theinstrument of standard contract application as a basis of law relationship among the economicactors. The nature of standard contract that is identical to the principle “take it or leave it” is aclear example of the difference of position that leads to a form of exploitation of consumers and form the opposition to the principles of the agreement in general. The proliferation of standard contract application in the community is an implication of freedom of contract principle that applied to the restrictions set forth in Article 1337 and Article 1339 of Civil Code. Although restrictions on the principle of freedom of contract has been regulated strictly, the application of standard contracts that happened in the community tend to be opposed to the principle of freedom of contract itself, especially in terms of the substance and implementation of the contract.This situation at last encourages the consumers protection both preventive and repressive legal protection. The mechanism of consumer dispute resolution is divided into three systems; consist of the peaceful settlement; settlement of disputes through public justice, or the settlement of disputes outside the courts through the Consumer Dispute Settlement Body (BPSK). The dispute resolution procedure through BPSK is divided into three stages namely, complain phase, trial phase and decision phase, while the court procedure is divided into stages of proposing a lawsuit, the reading a lawsuit by the plaintiff, the defendant answers on the plaintiff’s lawsuit, replik, duplik, and the examination of evidence, conclusions, and the judge’s decisionKeywords: Consumer Protection, Standard Contract, Transaction Law